2010
DOI: 10.1007/bf03195711
|View full text |Cite
|
Sign up to set email alerts
|

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken

Abstract: Visfatin is a peptide that is predominantly expressed in visceral adipose tissue and is hypothesized to be related to obesity and insulin resistance. In this study, a novel silent single-nucleotide polymorphism (SNP) was found in exon 7 of the chicken visfatin gene (also known as PBEF1) by single-stranded conformation polymorphism (SSCP) and DNA sequencing. In total, 836 chickens forming an F2 resource population of Gushi chicken crossed with Anka broiler were genotyped by XbaI forced RFLP, and the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In this study, a Gushi-Anka F 2 resource population as previously described by Han et al (2010Han et al ( , 2011 was used to investigate the allele frequency. The population was a cross of Gushi chicken and Anka broilers, representing the slow-growing and the fast-growing broiler, respectively.…”
Section: Resource Populations and Traits For Association Analysismentioning
confidence: 99%
“…In this study, a Gushi-Anka F 2 resource population as previously described by Han et al (2010Han et al ( , 2011 was used to investigate the allele frequency. The population was a cross of Gushi chicken and Anka broilers, representing the slow-growing and the fast-growing broiler, respectively.…”
Section: Resource Populations and Traits For Association Analysismentioning
confidence: 99%
“…A total of 860 chickens from a Gushi-Anka F2 resource population as previously described by Han et al (2010Han et al ( , 2011 were used to investigate the allele frequency. The flock was a cross of Gushi chicken, representing a slow-growing Chinese native chicken breed, and Anka broilers, representing a fast-growing broiler.…”
Section: Study Populationmentioning
confidence: 99%
“…Similarly, Fig. 1a showed that the allele A and C were both absent in LLH at rs314901473 and rs316142388, respectively, while individuals with these two alleles were reported to have better growth performance at early growth stage in F2 resource population made up of the reciprocal cross between Gushi chicken and Anka broilers and at late growth stage in Jinghai yellow chickens, respectively (Table 1) [17,22]. Although the frequency of allele A in CB was the highest among all seven chicken populations, the genotype GG was still the primary genotype in all chicken populations at rs314901473.…”
Section: Discussionmentioning
confidence: 89%
“…To characterize the genetic variations and genetic relationships among different populations using DNA markers, a total of 28 identified SNP markers, including 14 growth or carcass traits associated loci and 14 egg laying related genome positions, were selected from the previous reports [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. By using the MassArray technology, an Agena Bioscience MassARRAY System which is capable of efficiently genotyping tens to hundreds of SNPs with high accuracy, we detected the genotype frequency distributions of the 28 SNP markers in seven populations including four lowly selected as well as one moderately selected Sichuan native chicken populations, one commercial broiler line and one commercial layer line [34,35].…”
Section: Introductionmentioning
confidence: 99%